Managerial coaching to improve on organizational performance: A case study of a multinational company - Kuan, Chi Meng; Abu Bakar, Hassan (UUM Press, 2023)
BlastOne Malaysia Sdn Bhd, a multinational company incorporated in Malaysia is struggling to meet its organizational goals and objectives in the past few years; such as yearly sales target, profitability, staff turnover rate, product quality and customer satisfaction. This study aims to address the reasons behind the failure of the company in meeting its goals and objectives from the internal perspective focusing on its employees. Then, the study also aims to recommend the appropriate strategies and actions to be undertaken by the company in addressing these related issues. This study involves a detailed analysis of the business competitiveness of BlastOne Malaysia Sdn Bhd, based on the RBV Model (Resource-Based View), the I/O Model (Industrial Organization) and finally the SWOT Analysis. The findings revealed certain visible weaknesses in the competencies of the team members regarding their ability in goal setting and goal accomplishment. The findings also suggested that the team members are too focused on their daily problems and in doing so, failed to establish a positive behaviour to have a solution-focused mentality. As such, their inclinations toward the problem instead of the solution itself, has indirectly created a sense of demotivation amongst the employees. In countering the situation from the internal perspective and capabilities, this study adopted the GROW Coaching Model that has four main processes: namely Goal, Reality, Options and Will. The two key dimensions from the GROW Coaching Model, which are goal setting and solution-focused mentality, have the required elements in managing most of the internal weaknesses highlighted from the analysis done. The adoption of the GROW Coaching Model will prepare the company to be more competitive internally and at the same time, developing a strong coaching culture within the company.